Chemical Composition, Antioxidant, Antibacterial, and Antibiofilm Activities of Backhousia citriodora Essential Oil - Lim A.C.; Tang S.G.H.; Zin N.M.; Maisarah A.M.; Ariffin I.A.; Ker P.J.; Mahlia T.M.I. (MDPI, 2023)
antiinfective agent; antioxidant; essential oil; biofilm; chemistry; Escherichia coli; microbial sensitivity test; Myrtaceae; Staphylococcus aureus; Staphylococcus epidermidis; Anti-Bacterial Agents; Antioxidants; Biofilms; Escherichia coli; Microbial Sensitivity Tests; Myrtaceae; Oils, Volatile; Staphylococcus aureus; Staphylococcus epidermidis